Security Pricing in an Imperfect Capital Market - Mao, James C. T. (Journal of Financial and Quantitative Analysis, 1971)
A perfect capital market is a key assumption in recent theories of security pricing. It is assumed that the costs of transactions, information-gathering, and portfolio management are all zero, and that no investor is so large as to exert an appreciable effect on either the risk-free interest rate or the yield on risky securities. If, in this perfect capital market, investors have identical decision horizons and homogeneous expectations, then there is a unique optimal portfolio of risky securities. Since this unique portfolio must include every security in proportion to its relative valuation in the capital market, it is referred to as the “market” portfolio. When the capital market reaches equilibrium, the expected return of every security will be a linear function of the expected return of the market portfolio. From this relationship Lintner and Mossin have separately derived valuation formulas that express the market price of a security as a function of the security[s end-of-period expected value, its risk as measured by the variance and covariances of this end-of-period value, the market price of risk within the portfolio, and the risk-free rate of interest.